Microfriction Stir Welding of Aluminium Using ABB IRB 1410 Robot - R. Manoj Samson; R. Aravind; Solomon Jenoris Muthiya; Joshuva Arockia Dhanraj; Karthikeyan Velmurugan; Saw Lin Oo (Advances in Materials Science and Engineering)
Industry 4.0 industries are relying on automation processes using robots. Robots are multifunctional reprogrammable machines tuned to be used in any process with high accuracy and repeatability. The advent of intelligent technology allows better precision in the welding process. One such robotic welding process is the robot microfriction welding process which is slowly replacing conventional ones. Robot microfriction stir welding (RMFSW) process mainly relays on friction between the tool and material making it more suitable for joining metals in the industries such as automotive and aerospace applications. The robot-assisted MFSW process can provide better joints without human intervention. In this work, a shrinking flange has been designed and fabricated to grip the end effector with the robot. A microfriction stir welding tool was manufactured using EN24 and used to weld 1 mm thin aluminium 1100 sheets. Both the flange and MFSW tools were designed in SOLIDWORKS software. Taguchi L9 was designed with three factors such as motor speed, traverse speed, and plunging depth. The robot microfriction stirs welded samples had controlled bead width and depth of penetration. Mechanical results show an improvement in hardness after the welding process. TOPSIS optimization technique was carried out. The motor speed of 20,000 rpm, traverse speed of 2 mm/sec, and plunge depth of 0.7 mm were found to be the best-optimized parameters.